Cooperative physisorption and chemisorption of hydrogen on vanadium-decorated benzene. Issue 62 (13th October 2020) - Ma, Li-Juan; Han, Ting; Jia, Jianfeng; Wu, Hai-Shun
Abstract : We provide a comprehensive picture of hydrogen interaction with VC6 H6 and a way of designing promising hydrogen storage materials. Abstract : 3d TM-decorated carbon composites have been proved to be a new generation of hydrogen storage materials. However, detailed hydrogen storage mechanisms are still unclear. Investigation of the H2 dissociation and H migration on the 3d TM-decorated six-membered carbocycles is very critical for better understanding the hydrogen storage mechanism. In this paper, the processes of chemisorption and physisorption of multiple H2 molecules on synthesized VC6 H6 were simultaneously investigated for the first time. The Gibbs free energy calculations show that the optimal chemisorption pathway with the hydrogen storage capacity of 5.97 wt% is exothermic by 2.83 kcal mol −1 . Both the continuous hydrogenation giving the product of VC6 H11 –3H and reverse dehydrogenation could run smoothly at room temperature. The physisorption with a hydrogen storage capacity of 4.48 wt% will be exothermic by 13.49 kcal mol −1 . The H2 molecules can be physisorbed at any temperature under 416 K and readily desorbed above 480 K at 1 atm. In summary, physisorption and chemisorption synergistically boost the hydrogen storage property of complex VC6 H6 . Our study provides a comprehensive picture of the interaction between hydrogen and VC6 H6 and opens a new window for optimizing the future hydrogen storage materials.